MOCVD growth and characterization of quantum dots for mid-infrared emission - Yin, Zong You (2008)
This PhD project mainly covers three themes: development of metal-organic chemical vapor deposition (MOCVD) growths of high density and uniform compound semiconductor quantum dots (QDs); development of mid-infrared (mid-IR) emissive InAs QD structures and study of their properties; and the post-growth energy band gap tuning of QD structures using QD intermixing technology. High density and uniform semiconductor QDs are very important in developing novel electronic and optoelectronic devices and in physics studies. In this project, MOCVD growth of InAs QDs has been developed under safer growth conditions, i.e. using the low-toxic Tertiarybutylarsine (TBAs) as group-V source to replace the high-toxic AsH3 and using inertial N2 as the carrier gas to replace the explosive H2. Effects of the growth conditions on the InAs QD formations have been investigated. Because of the nucleation process, high dot density and narrow dot size dispersion of the QDs are very difficult to be formed in conventional Stranski-Krastanow (SK) self-assembly growth. In this project, a new two-step growth method has been developed for forming QDs with higher density and more uniformity. In this new QDs growth method, QDs are formed in two steps during the epitaxy growth: a growth rate dependent QDs nucleation in step 1 growth followed by the kinetically self-limited QDs formation in step 2 growth. Compared with InAs QDs formed by the conventional SK self-assembly growth method, morphology of the InAs QDs formed by using this two-step growth method is greatly improved. High density InAs QDs have been formed using this two-step growth method. The QDs surface coverage reaches 60% and the dot-size dispersion is as narrow as 1 nm. The mechanism of this improvement in two-step growth of QDs has been discussed. In this project, MOCVD growths of InAs QDs for mid-infrared emissions have been developed. By using an 8 kp theoretical model, transition energies of the InAs/InGaAs/InP QD structure have been calculated under a quantum well approximation. In this calculation, lattice mismatch strain between the InAs and InGaAs barrier layers is considered. Based on the theoretical calculated results, mid-IR emissive InAs/InGaAs/InP QD structures have been designed. By employing the InGaAs barriers in InAs/InP QD structure, emission wavelength of the QD structures has been extended. Emission wavelength of the InAs/InGaAs/InP QD structures reaches >2.2 m when the indium content of the InGaAs square barrier is >0.72. By using the In0.53(0.53+y)Ga0.47(0.47-y)As graded barriers in the QD structure, the wavelength of the QD structure reaches >2.35 m at 77 K when the indium gradation y =0.27. This QD structure has been grown by MOCVD using the two-step growth method for growing the QDs layer. The measured emission wavelength from the QD structure matches the calculated transition energy well. This is the longest inter-band transition emission wavelength from the InAs QD structures reported so far. Finally, post-growth energy band gap tuning of the InAs QD structures has been investigated using argon plasma enhanced QD intermixing technology. Band gap energy of the InAs QD structure has been successfully tuned by as large as 128 meV. Spatial selective intermixing of the InAs QD structure has been investigated by employing a SiO2 mask on top surface of the sample during the intermixing. By controlling the plasma exposure time or the annealing temperature, multi-wavelengths with 50-nm wavelength separation across one wafer have been achieved for InAs/InGaAs/InP QD structures. This paves a way to realize multi-functional monolithic integration of optoelectronic circuits.